ON SOME PROPERTIES OF ACRONYMS USED IN KOREAN - Borowiak, Anna (International Journal of Korean Humanities and Social Sciences, 2016)
Abbreviation process in Korean applies to both lexical and grammatical units (cf. Borowiak 2015). This article however focuses only on one type of the former, namely acronyms. The formations in question are created in the lingual process, which could be called acronymization and are a convenient means of expression widely used in various fields of contemporary civilization such as science and technology, economy and public life, media, marketing etc. Despite their undeniable popularity the subject of acronymology is given relatively little attention in relevant literature, which concentrates mainly on morpheme-based word-formation and thus downplays acronyms as being e.g. unpredictable ‘non-rule governed innovations’ (cf. Bauer 2001). The 20th century however, as Szadyko (1997: 127) points out, belongs to acronyms – that is why the subject definitely deserves more attention. The aim of this article is to identify, analyze and classify acronyms used in Korean. Abbreviations of this particular type, as this paper will attempt to show, although rarely and rather briefly discussed, are in fact extremely numerous in Korean language. Taking into consideration their number and variety the attempt to classify them according to origin, fields of usage, lexical meaning and familiarity, the method of formation, graphemic form and the type of founding constituents is made.